Video Games Exposure and Sexism in a Representative Sample of Adolescents - Bègue, Laurent; Sarda, Elisa; Gentile, Douglas A.; Bry, Clementine; Roché, Sebastian (Frontiers in Psychology, 2017)
Research has indicated that many video games are saturated with stereotypes of women and that these contents may cultivate sexism. The purpose of this study was to assess the relationship between video game exposure and sexism for the first time in a large and representative sample. Our aim was also to measure the strength of this association when two other significant and well-studied sources of sexism, television exposure and religiosity, were also included in a multivariate model. A representative sample of 13520 French youth aged 11–19 years completed a survey measuring weekly video game and television exposure, religiosity, and sexist attitudes toward women. Controlling for gender and socioeconomic level, results showed that video game exposure and religiosity were both related to sexism. Implications of these results for future research on sexism in video games are discussed.